Synergistic effect of Glomus mosseae and Burkholderia Fungorum on growth and productivity of sorghumbicolor (Funded Work) - MEDHATITHI SEN,; SIKHA DUTTA, (International Journal of Pharma and Bio Sciences, 2018)
Soil microbes play an important role in increasing soil fertility as well as enhancing growth and productivity of plants. The dominant soil microbes are entophytic fungi and plant growth promoting bacteria. The interaction between soil microbes and host plants increases the nutritional level of plants. The effect of two microorganism, Glomus mosseae (AM) and Burkholderia fungorum (PGPR)on the morphological and physiological parameters of Sorghum bicolour (Jowar) was studied under pot culture. The AM inoculated plants exhibited maximum amount of chlorophyll-a, b, carbohydrate, protein, phosphorus, amino acid and reducing sugar content compared to the non-inoculated plants of control set and as well as PGPR inoculated plants even after 90 days of inoculation. Simultaneously, on the other hand, shoot and root length, dry and fresh weight, leaf area, leaf number, grain yield were recorded to be more in the plants which were inoculated with both the microbes i.e. VAM and PGPR than in the plants inoculated either with VAM or with PGPR. The results suggest that VAM–PGPR interaction in host plants is suggestive not only for boosting the growth and development of the plants but also for the improvement of yield of the crop the plant, Sorghum bicolour.